2011
DOI: 10.1523/jneurosci.0698-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Caspase-9 Inhibitor Reduces Caspase-6-Dependent Axon/Neuron Loss and Improves Neurological Function after Stroke

Abstract: Despite extensive research to develop an effective neuroprotective strategy for the treatment of ischemic stroke, therapeutic options remain limited. While caspase-dependent death is thought to play a prominent role in neuronal injury, direct evidence of active initiator caspases in stroke and the functional relevance of this activity have not previously been shown. Employing an unbiased caspase-trapping technique in vivo, we isolated active caspase-9 from ischemic rat brain within 1 hour of reperfusion. Patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
84
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 50 publications
2
84
1
Order By: Relevance
“…Oxidative stress, a trigger for apoptosis, induced by the addition of hydrogen peroxide in HEK 293/Tau cells, increases active caspase-6 and caspase-3 activity (72). An increase in caspase-6 activity has also been documented in global brain ischemia (73) Caspase-6 Helix-Strand Interconversion and acute ischemic stroke (74), where slight intracellular acidification has been observed to acidify slightly to pH 6.43 (75). Although the precise role of the two-state conformations of caspase-6 is still not known, pH changes in the context of neurodegeneration could conformationally enrich caspase-6 in either helical or strand conformations.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, a trigger for apoptosis, induced by the addition of hydrogen peroxide in HEK 293/Tau cells, increases active caspase-6 and caspase-3 activity (72). An increase in caspase-6 activity has also been documented in global brain ischemia (73) Caspase-6 Helix-Strand Interconversion and acute ischemic stroke (74), where slight intracellular acidification has been observed to acidify slightly to pH 6.43 (75). Although the precise role of the two-state conformations of caspase-6 is still not known, pH changes in the context of neurodegeneration could conformationally enrich caspase-6 in either helical or strand conformations.…”
Section: Discussionmentioning
confidence: 99%
“…While intriguing given the evidence of APP accumulation in injured axons, whether this system is applicable to ischemic axonal injury remains unclear. Recent work by Akpan et al [59] demonstrated that caspase-9 activation occurs early after transient middle cerebral artery occlusion (tMCAO) triggering activation of the caspase-6-dependent axonal degeneration pathway in the ischemic penumbra. In a novel translational approach, this group used intranasal caspase-9 inhibition to block axonal degeneration after stroke and improve functional recovery.…”
Section: The Back: Progressive Axonal Degeneration After Strokementioning
confidence: 99%
“…Nikolaev et al showed that the inhibition of DR6 protects axons and neurons by inhibiting caspase-6 and caspase-3 activation after trophic deprivation [14]. Some authors report that the inhibition of caspase-9 reduces caspase-6-dependent axon and neuron loss and improves neurological function after stroke [18]. Other authors have found that caspase-6 inhibition enhances both survival and regeneration of injured retinal ganglion cells [19].…”
Section: Axon Regeneration Is Inhibited In Nerve Injury Diseasesmentioning
confidence: 99%